2007
DOI: 10.1590/s1415-47572007000300017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Brazilian wild rice (Oryza glumaepatula Steud., Poaceae) populations analyzed using microsatellite markers

Abstract: Knowledge of the genetic structure and diversity of natural populations is important in developing strategies for in situ and ex situ conservation. We used eight microsatellite loci to estimate genetic structure and investigate within and between population genetic variation in eleven Brazilian wild rice (Oryza glumaepatula) populations. The study showed the following genetic diversity parameters: average number of 3.1 alleles per locus; 77.3% polymorphic loci; 0.091 observed heterozygosity and 0.393 gene dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
13

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 29 publications
(60 reference statements)
6
30
0
13
Order By: Relevance
“…Thus, considering six loci and four enzymatic systems, the mean number of alleles per locus ranged from 1.00 to 1.50, with a mean of 1.21 alleles per locus (Table 3), in agreement with the previous studies with isozyme (Akimoto et al, 1998;Buso et al, 1998) and microsatellite markers (Brondani et al, 2005) in O. glumaepatula. Karasawa et al (2007), however, observed a mean of 3.09 alleles per locus with microsatellites for this species. The percentage of polymorphic loci ranged from 0.0 to 50.0%.…”
Section: Genetic Diversitymentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, considering six loci and four enzymatic systems, the mean number of alleles per locus ranged from 1.00 to 1.50, with a mean of 1.21 alleles per locus (Table 3), in agreement with the previous studies with isozyme (Akimoto et al, 1998;Buso et al, 1998) and microsatellite markers (Brondani et al, 2005) in O. glumaepatula. Karasawa et al (2007), however, observed a mean of 3.09 alleles per locus with microsatellites for this species. The percentage of polymorphic loci ranged from 0.0 to 50.0%.…”
Section: Genetic Diversitymentioning
confidence: 63%
“…However, the authors observed greater intrapopulational than interpopulational variability, a pattern usually found in the crossfertilized populations, which was explained considering the life history characteristics of this species. Studies of the genetic structure of O. glumaepatula populations were also recently conducted with microsatellite markers (Karasawa, 2005;Karasawa et al, 2007;Brondani et al, 2005;Silva et al, 2007), showing high values for F ST and R ST , suggesting a higher interpopulational variability, as well as the predominance of a selffertilizing breeding system. The purpose of this study, using isozymic markers, was to provide further information on the genetic diversity and genetic structure of 14 O. glumaepatula populations, originated from the hydrographic basins of the Amazon and of Rio Paraguay in the Pantanal ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Este número foi inferior aos obtidos por outros autores na mesma espécie. Karasawa et al (2007), utilizando oito locos de microssatélites, amplificaram 80 alelos em 11 populações de O. glumaepatula (total de 330 indivíduos), sendo a média de dez alelos por loco, enquanto Brondani et al (2005) analisando 10 locos SSR obtiveram 103 alelos em 30 populações de O. glumaepatula (total de 440 indivíduos), uma média de 10,3 alelos por loco observado.…”
Section: Discussionunclassified
“…Karasawa et al (2007), estudando 11 populações com maior número de indivíduos amostrados por população (variando de 17 a 35) e utilizando oito locos de SSR, observaram alelos privados em nove populações, variando de 1,0 a 8,0 por população. Por outro lado, Brondani et al (2005) (Slatkin 1995) em Oryza glumaepatula.…”
Section: Discussionunclassified
See 1 more Smart Citation